1999
DOI: 10.2190/0ky0-p54v-kfdb-9vcr
|View full text |Cite
|
Sign up to set email alerts
|

“How Will You be Remembered after You Die?” Gender Discrimination after Death Twenty Years Later

Abstract: Obituaries in four major metropolitan newspapers (the Chicago Tribune, the Los Angeles Times, the Miami Herald, and the New York Times) are examined for gender differences and compared to a study conducted over twenty years ago by Kastenbaum, Peyton, and Kastenbaum. Not unlike the original study, men receive significantly more obituaries than women in each of the four papers, their obituaries are longer (except for the Miami Herald), and they are accompanied by significantly more photographs (except for the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In an original study, Robert Kastenbaum, Peyton, & Kastenbaum (1977) found a 4–1 ratio in the obituaries published in two main American newspapers, The Boston Globe and The New York Times (although the same study discovered a relatively egalitarian distribution of death notices in the same sample). Two decades later, Robin D. Moremen and Cathy Cradduck (1999) found a similar ratio (78% of obituaries for men) after analyzing four major American metropolitan newspapers. Curiously, in The New York Times , the gender bias increased significantly from the original study.…”
Section: Resultsmentioning
confidence: 85%
“…In an original study, Robert Kastenbaum, Peyton, & Kastenbaum (1977) found a 4–1 ratio in the obituaries published in two main American newspapers, The Boston Globe and The New York Times (although the same study discovered a relatively egalitarian distribution of death notices in the same sample). Two decades later, Robin D. Moremen and Cathy Cradduck (1999) found a similar ratio (78% of obituaries for men) after analyzing four major American metropolitan newspapers. Curiously, in The New York Times , the gender bias increased significantly from the original study.…”
Section: Resultsmentioning
confidence: 85%
“…However, prior research has suggested that English Wikipedia articles have systematic biases against women, historic figures, and people from the Global South [6,18,34], a tendency that emulates biases observed in the selection of subjects for obituaries [17,31,37]. If this is true, we expect that posthumous editing activity will show significant differences based on the gender, and birthplace of individuals.…”
Section: Biases In Attentionmentioning
confidence: 91%
“…Editorial staff must make decisions about who to cover, what content to include, and the overall style [38,39]. Scholarship has noted journalistic bias that privileges men [31], cultures that are proximate to the newspaper [17], as well as stylistic differences across different countries [37].…”
Section: Obituaries As Journalistic Practicementioning
confidence: 99%
“…Gender bias against women was observed in newspaper obituaries with women receiving fewer obits, shorter obits, and fewer accompanying photographs (Kastenbaum, Peyton, and Kastenbaum, ; Moremen and Cradduck, ). Gender bias in cemeteries was observed in frequent references to women in terms of their familial relationships (“the wife of”) and in the inclusion (or omission) of surnames (Abel, ).…”
Section: Discrimination After Deathmentioning
confidence: 99%